Electrical impedance and conduction mechanism analysis of biopolymer electrolytes based on methyl cellulose doped with ammonium iodide - Salleh, N.S.; Aziz, S.B.; Aspanut, Z.; Kadir, M.F.Z. (Springer Verlag (Germany), 2016)
In the present study, the potential of methyl cellulose (MC) as biopolymer electrolyte (BPE) will be studied extensively by means of conductivity and the conduction mechanism. BPE films based on MC doped with ammonium iodide (NH4I) salt were prepared by solution-casting method. X-ray diffraction (XRD) explains that the conductivity enhancement of the electrolytes is affected by the degree of crystallinity. Field emission scanning electron microscopy (FESEM) analysis shows the difference in the electrolyte’s surface with respect to NH4I. On addition of 40 wt.% of NH4I, the highest room temperature conductivity of (5.08 ± 0.04) × 10−4 S cm−1 was achieved. The temperature dependence relationship for the salted electrolyte was found to obey the Arrhenius rule where R2 ∼1 from which the activation energy (Ea) was evaluated. The dielectric study analyzed using complex permittivity ε* for the sample with the highest conductivity at elevated temperature shows a non- Debye behavior. These salted electrolytes follow the correlated barrier hopping (CBH) model.